Using the Nanvix Operating System in Undergraduate Operating System Courses - Penna, Pedro Henrique; Castro, M.; Freitas, H.; Méhaut, Jean-François; Caram, Joao (2017 VII Brazilian Symposium on Computing Systems Engineering (SBESC), 2017)
Operating Systems (OSs) have an important position in the Computer Science curriculum. When students face this subject, they study core concepts, mechanisms and strategies that apply to several fields. To support practical lectures in an OSs course, instructors may adopt an OS on which students can work, exercising their knowledge and enhancing their practical skills. In this context, we present Nanvix, a new OS designed to address this use in undergraduate OSs courses. We introduce a flexible assignment-based teaching methodology for our OS, and we assess the effectiveness of this methodology by applying it in the OSs course of the Pontifical Catholic University of Minas Gerais. When using Nanvix, the average score of the students in the course increased in 11.2%, and the failure rate dropped 47.7%. Moreover, we observed that with Nanvix students got more motivated and interested in the OSs field.